Pengaruh waktu pelapisan back oxide terhadap ketahanan korosi dan sifat mekanik pada baja AISI 4340 - Devi Eka Septiyani Arifin; Alda Diva Meidina (BKS-TM Indonesia, 2026)
Blackening, also known as Black Oxide coating, is a conversion coating method that forms a black oxide layer on the surface of steel used in industry to enhance corrosion resistance, aesthetics, and mechanical properties. This study aims to determine the effect of coating times (blackening) of 10 minutes, 30 minutes, and 60 minutes at a temperature of 140 °C on the corrosion resistance, tensile strength, and coating thickness of AISI 4340 steel. The results showed that the variations succeeded in forming a uniform black layer that adhered well to the surface, while good corrosion resistance was obtained at 30 minutes. The thickness of the layer formed was directly proportional to the coating time, increasing from 13.06 µm at 10 minutes to 18.55 µm at 60 minutes. In contrast, the tensile strength showed a different trend of results at 10 minutes, reaching the highest tensile strength of 1684 MPa; however, the tensile strength decreased at 30 minutes and 60 minutes. This decrease in tensile strength value was due to the number of hydrogen atoms formed during the dehydrogenation process. These atoms diffuse and become more entrapped in the steel's atomic structure with longer plating times. This difference in duration results in the dehydrogenation process having different rates of complete removal of trapped hydrogen atoms at each time interval, resulting in a decrease in tensile strength.